ScnML models single-cell transcriptome to predict spinal cord neuronal cell status - Liu, Lijia; Huang, Yuxuan; Zheng, Yuan; Liao, Yihan; Ma, Siyuan; Wang, Qian (Frontiers in Genetics, 2024)
In the manuscript "ScnML models single-cell transcriptome to predict spinal cord neuronal cell status", the authors have integrated scRNA-seq and machine learning to spinal cord nerve cells.The manuscript is well written, and the models performance metrics are impressive. There is no doubt that the tool will be useful in medicine research. I think after fully addressing my comments, this MS will have the merit for contribution in the related area.The full list of 210 marker genes with annotations is required as a supplementary Table .